The Physiological Response of Madura Cattle to Dry Matter Consumption Levels on Maintenance at Different Altitude Locations - Bahrur, Khairul Anam; Umar, Malikah; Hidayati, Nurul (Universitas Halu Oleo, 2022)
This study aims to know the physiological response of Madura cattle to the level of DM consumption with the same maintenance pattern and the same physiological conditions at different altitudes, namely in lowland areas (Tlanakan District, Pamekasan Regency) and medium plains (Tembalang District, Semarang City). Tlanakan sub-district has an altitude of 0-22 m above sea level, and Tembalang district is 160-250 m above sea level. The results of the study showed that the level of DM consumption at different altitudes gave significantly different results (p